GENESIS OF THE POLISH-UKRAINIAN RELATIONS IN 1991-2017 - Бойчук, О. І.; Гринюк, І. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The question of evolution of Polish-Ukrainian bilateral relations is investigated. Based on the previous academic research, the periodization of Polish-Ukrainian relations has been improved in accordance with current events. It is noted that the bilateral relations began immediately after the restoration of independence by both countries. However, in the early 1990s, bilateral relations were not very active. The reason for this was the processes of economic transformation that took place after the fall of the Soviet economic system, which led to a weak economic situation. The ideological germs of the Polish-Ukrainian understanding originate from the activities of the publication «Culture» around which the Polish and Ukrainian liberal elites were concentrated, which aimed to begin the process of understanding between the two peoples. It is noted that in the 2000s, Polish-Ukrainian relations were mainly connected with the presidencies of V. Yushchenko and A. Kwaśniewski, and later L. Kaczynski. Personalism in relations had positive results, which contributed to an intensification of dialogue between countries. At the end of Yushchenko’s term, relations fell asleep, which was due to the events in Ukraine. Nevertheless, the Eastern Partnership was launched during this period. After 2014, bilateral relations entered a phase of stable understanding. The formula «forgive and apologize» was chosen, thus referring to the well-known exchange of letters between the Polish and German bishops. Attention is drawn to the fact that the President Petro Poroshenko tried to strengthen bilateral relations. The weakness of Polish-Ukrainian relations is cooperation at the society level. It is the deepening of the social level that should contribute to the stability of relations and reduce the impact of the negative phenomena related to the political conflict, which are occasionally present in Polish-Ukrainian relations, especially in the context of historical policy in recent years.